Analysis of Student Difficulties in Istima' Learning at Imam Bonjol State Islamic University Padang - Aqilah, Shintia; Febriani, Suci Ramadhanti; Mustafidah, Hidayatul; Nardi, Hanifa (Universitas Islam Tribakti Lirboyo, Kediri, 2025)
Maharatul istima’ are the first skills a person performs in language. This ability begins at an early age as humans attempt to understand their surroundings. In learning Maharatul Istima' students are required to need more than just hearing, but also a deep thought process to analyze the message conveyed. This type of research is qualitative research with data collection techniques using observation, interviews and documentation to students of Arabic Language Education at Imam Bonjol Padang State Islamic University. The aim of this research is to find out how Maharatul Istima' is taught, the factors of difficulties experienced by students and the efforts made to reduce these difficulties. From the research results, it can be concluded that Maharatul Istima' learning is carried out by practicing using audio-lingual or audio-visual, which there are conversations in groups or pairs. The difficulty of learning Maharatul Istima' is influenced by three factors, namely linguistics which includes sound system, sentence structure and mufrodat, then non-linguistic factors which include the student's educational background, the environment and the lack of learning Maharatul Istima' then the learning media used is not in accordance with the student's abilities. . The efforts that can be made to overcome difficulties in learning Maharatul Istima' are by using appropriate audio media and effective learning methods that help facilitate students in receiving information that is heard.